Clinical applications of perfusion-weighted magnetic resonance imaging in neurological disorders - Falah, Yasser (2019)
The research presented in this thesis represents my passion for developing magnetic resonance imaging (MRI) techniques in neurological disorders. Arterial spin labeling (ASL), a non-contrast MRI method, is used as a tool to characterise different patients groups with the view to develop understanding of disease processes, confirm diagnosis, and monitor progression.